The relationship between oxLDL, sLOX-1, PCSK9 and carotid intima-media thickness in patients with prediabetes and type 2 diabetes - Zeki Dogan; Abdulhalim Senyigit; Sinem Durmus; Canan Duvarcı; Remise Gelişgen; Hafize Uzun; Omur Tabak (Scientific Reports)
Abstract Affection of vascular structures is a known complication in diabetes and prediabetes. Subclinical atherosclerosis begins to develop years before both cardiovascular and cerebrovascular diseases become symptomatic. The aim of this study was to evaluate the relationship between circulating oxidized LDL (oxLDL), soluble lectin-like oxidized LDL (sLOX)-1 and proprotein convertase subtilisin/kexin type 9 (PCSK9) levels and carotid intima-media thickness (CIMT) in patients with prediabetes and T2DM. We recruited 50 T2DM patients with macrovascular complications, 50 T2DM patients with uncomplicated, 50 prediabetes patients, and 50 healthy participants. The common carotid arteries were visualized by high-resolution B-mode carotid artery ultrasonography. Measurement of serum oxLDL, sLOX-1 and PCSK9 levels were assessed by using a commercially available human enzyme-linked immunosorbent assay (ELISA) method. Homeostasis model assessment for insulin resistance (HOMA-IR) was also calculated. Circulating LDL-C, oxLDL, sLOX-1 and PCSK9 levels were significantly higher in T2DM patients with macrovascular complications compared to control group, prediabetes and uncomplicated diabetes. There was significant difference, especially between the controls and the T2DM patients with macrovascular complications. The CIMT increased progressively from control through to T2DM. Both right and left CIMT also showed significant differences between the groups of prediabetes versus uncomplicated diabetes at p < 0.001 showing progressive increase in vascular involvement with progression of disease. There was a positive correlation between PCSK9 levels with LDL-C, oxLDL, sLOX-1, and CIMT. ROC curve analyses showed that PCSK9, as well as oxLDL and LOX-1, was a strong predictor of T2DM with high sensitivity and specificity. In this study, we found that oxLDL, sLOX-1 and PCSK9 levels were significantly associated with carotid intima-media thickness. Our findings suggest that these biomarkers may be used as potential markers for the assessment of cardiovascular risk in patients with prediabetes and type 2 diabetes.